Sustainable solutions for healthcare facilities: examining the viability of solar energy systems - Al-Rawi, Omar F.; Bicer, Yusuf; Al-Ghamdi, Sami G. (Frontiers in Energy Research, 2023)
The healthcare sector is responsible for a significant portion of global carbon dioxide emissions, accounting for approximately 5% of the total. As energy demand in the sector continues to rise, sustainable solutions are urgently needed. Hospitals and healthcare facilities require a range of engineering services, including heat ventilation and air conditioning systems, hot and domestic water supply systems, and backup electricity systems. These energy-intensive services offer an excellent opportunity to integrate renewable energy sources and reduce the carbon footprint of healthcare facilities. This study presents a case study of a hospital located in the Gulf Cooperation Council (GCC) that utilizes a solar-collected water-heated system. The research aims to investigate the impact of adding multi-solar collector and photovoltaic systems to healthcare facilities, analyze the system's thermodynamic efficiency in terms of energy and exergy, assess its technical and economic viability, and gauge the adoption rate of solar systems by healthcare technical departments. The results demonstrate that the solar thermal system provides around 12% of the total energy needed for the hot water system, while the solar PV system contributes approximately 29.6% of the total load for the HVAC system. This study explores the potential of using solar energy systems in healthcare facilities in the GCC region, analyzing their technical, thermodynamic, and economic viability. It promotes the adoption of solar systems in GCC and Middle East healthcare facilities and identifies research gaps related to solar systems implementation in healthcare facilities in the GCC. The study highlights the potential benefits of solar energy systems in terms of energy efficiency, cost savings, and environmental sustainability, with implications for healthcare facilities in the region and beyond. By utilizing renewable energy in healthcare facilities, the sector can reduce its carbon footprint and contribute to a more sustainable future.